Development and flight-testing of modular autonomous cultivation systems for biological plastics upcycling aboard the ISS - Xin Liu; Pat Pataranutaporn; Benjamin Fram; Allison Z. Werner; Sunanda Sharma; Nicholas P. Gauthier; Erika Erickson; Patrick Chwalek; Kelsey J. Ramirez; Morgan A. Ingraham; Natasha P. Murphy; Krista A. Ryon; et al. (npj Microgravity, 2025)
Abstract Cultivation of microorganisms in space has enormous potential to enable in-situ resource utilization (ISRU) Here, we develop an autonomous payload with fully programmable serial passaging and sample preservation, termed the Modular Open Biological Platform (MOBP), and flight-test the MOBP aboard the International Space Station (ISS) by conducting enzymatic and microbial plastics upcycling experiments. The MOBP is a compact, modular bioreactor system that allows for sustained microbial growth via automated media transfers, such as those for sample collection and storage for terrestrial analyses, and precise data monitoring from integrated sensors. The MOBP was flight-tested with two experiments designed to evaluate biological upcycling of the plastic poly(ethylene terephthalate) (PET). The bioproduct βKA can be polymerized into a nylon-6,6 analog with improved properties for use in the production of a variety of materials. We posit the MOBP will aid in democratizing the execution of synthetic biology in spaceflight towards enabling ISRU.